In-Vitro Characterization of the Aerosolized Dose During Non-Invasive Automatic Continuous Positive Airway Pressure Ventilation. Issue 1 (June 2016) - Hassan, Ahmed; Rabea, Hoda; Hussein, Raghda; Salah Eldin, Randa; Abdelrahman, Maha; Said, Amira; Salem, Heba; Abdelrahim, Mohamed
Abstract Introduction Many devices (e.g., nebulizers and spacers) are used to deliver aerosol in a non-invasive ventilation circuit (NIV) without any special recommendation. The aim of the present work was to compare the doses delivered from seven different aerosol delivery systems when placed in the NIV using automatic continuous positive airway pressure (Auto-CPAP). Methods Three spacers and three vibrating mesh nebulizers were compared to a Sidestream jet nebulizer (SIDE). Each device was placed proximal to a breathing simulator in a standard NIV circuit with a 500 ml tidal volume, 15 breaths/min and a 1:3 inspiratory-expiratory ratio. Two ml of salbutamol solution containing 10, 000 μg was nebulized using Aerogen Pro (PRO), Aerogen Solo (SOLO), NIVO and SIDE. Twelve metered dose inhaler doses, containing 100 μg salbutamol each, were delivered using AeroChamber MV (AC), AeroChamber Vent (VC) and AeroChamber Mini (MC). Total emitted dose (TED) and its percentage were determined. Aerodynamic droplet characteristics were measured using cooled Andersen Cascade Impactor. Results The vibrating mesh nebulizers used had significantly more (p  < 0.001) TED compared to the jet nebulizer. The spacers used had higher TED % (p  < 0.001) compared to the nebulizers. The fine particle fraction of SIDE was the highest (p  = 0.021) and mass median aerodynamic diameter of the spacers was the smallest (p  = 0.001). The fine particle dose from vibrating mesh nebulizers was the greatest (p  = 0.02). Conclusions Aerosol delivery in Auto-CPAP NIV is feasible; however, aerosol delivery method should be chosen or substituted with care. 2 mg delivered from a spacer would be equivalent to 3 mg nebulized from a vibrating mesh nebulizer and 5 mg nebulized from a Sidestream.